Tumorigenic role of podoplanin in esophageal squamous-cell carcinoma - ., Nur Rahadiani; Ikeda, Jun-ichiro; Makino, Tomoki; Tian, Tian; Qiu, Ying; Mamat, Suhana; Wang, Yi; Doki, Yuichiro; Aozasa, Katsuyuki; Morii, Eiichi (Society of Surgical Oncology, 2010)

(untitled)
Background. Podoplanin, a mucin-type transmembrane glycoprotein, is thought to be one of the cancer stem cell markers for squamous-cell carcinoma of the vulva. The objectives of the present study were to examine the role of podoplanin in esophageal squamous-cell carcinoma (ESCC). Methods. Expression of podoplanin was examined immunohistochemically in 61 cases of ESCC that had not been treated with chemotherapy or radiotherapy before surgery. Because cancer stem-cell quantities have been reported to increase with chemotherapy and radiotherapy, cases in patients who did not receive such prior therapies were included in this study. Cases with[10% tumor cells showing signals for podoplanin were categorized as podoplanin high, and the others were classified as podoplanin low. The effects of podoplanin on the behavior of cancer cells were evaluated in ESCC cell lines in which podoplanin expression was knocked down. Results. To examine whether podoplanin could be used as a cancer stem cell marker for ESCC, podoplanin-positive and podoplanin-negative fractions were sorted separately from the ESCC cell line and cultured. Podoplanin-positive ESCC cells yielded both podoplanin-positive and podoplanin- negative cells, whereas few cells were obtained from podoplanin-negative ESCC cells. When podoplanin expression was knocked down, ESCC cell lines became vulnerable to anticancer drugs and showed defective invasion and tumorigenic activities. Nineteen (31.1%) of 61 cases were categorized as podoplanin high. Podoplaninhigh cases were correlated with T category, stage of disease, lymphatic and vascular invasion, recurrence, and prognosis of patients. Podoplanin-low cases showed better overall and disease-free survival. Conclusions. There is a role for podoplanin in tumorigenesis and malignant progression in ESCC. Cancer cells comprise a heterogeneous group of cells, among which only a small population of cells possesses the ability to reconstitute a whole tumor.1–3 This population, called cancer stem cells (CSCs), efficiently forms colonies in semisolid culture and is xenotransplantable in nonobese diabetic/severe combined immunodeficiency (NOD/SCID) mice.4 CSCs were first identified in leukemia and subsequently isolated from solid tumors, such as those of breast, brain, prostate, melanoma, colon, pancreas, head/neck, liver, and gastric cancers.5–15 CSCs are known to be resistant to chemotherapy and radiotherapy and are more invasive than non-CSCs. Recognition of CSCs and their efficient elimination may be a valuable strategy for treatment of cancers. Therefore, studies to search for markers of CSCs have been performed. First, successful isolation of CD34? CD38- leukemic stem cells was reported.5 However, subsequent studies showed that markers for CSCs differ among cancers originating from different organs. Atsumi et al. reported that podoplanin, a mucin-type transmembrane glycoprotein, is a possible candidate CSC marker for squamous-cell carcinoma (SCC).16 Cultured cells from the SCC cell line A431, which is derived from the vulva, consist of two populations: podoplanin-positive and podoplanin-negative cells. CSCs are known to produce both CSC and non-CSC,